A Game Analysis of the Evolution of China–US Trade Friction Based on "Differential Pattern" and "Group Pattern". (10th March 2023) - Shen, Zhifeng; Xia, Yifan; Wang, Wei; Li, Zhihui; Ha, Hun‐koo
Abstract : In the context of Russia's special military operation against Ukraine, the purpose, scope, and final outcome of the China–US trade frictions are highly dynamic, complex, and uncertain. Combining the 4‐year trend of US–China trade frictions reveals that the China and United States are in a continuous process of exploring their own dominant decisions, so the evolutionary game is an ideal way to analyze the trend of China–US trade frictions. In the China–US trade frictions game, it is difficult for the other country to make a dominant decision without the participation of other countries or "standing on one's side." At present, while China and the United States are negotiating, one's absolute energy is to spare no effort to persuade or coerce a third party to "stand on one's side" or not to "stand on one's side." Therefore, the evolutionary game method, combined with the differential pattern and the group pattern theory, may be a feasible research design for a comprehensive analysis of the purpose of China–US trade frictions, the scope and duration of China–US trade frictions. This research is not only innovative from a theoretical perspective, but the results are also highly predictive and practical.